PEMBELAJARAN GI DAN GI-PROBLEM POSING (GI-PP) PADA MATA KULIAH KALKULUS LANJUT DITINJAU DARI SIKAP MAHASISWA TERHADAP MATEMATIKA - Maharani, Swasti (IKIP PGRI MADIUN, 2015)
The objectives of this research were to find out: (1) which learning model of the GI or GI-ProblemPosing results in a better learning achievement; (2) which studentsâ attitudes of thepositive, neutral, or negative types results in a better learning achievement; (3) in each studentsâattitudes, which learning model of the GI or GI-Problem Posing results in a better learningachievement; and (4) in each learning model, which studentsâ attitudes of the positive, neutral, ornegative types results in a better learning achievement. This research used the quasi experimental research method with the factorial design of 2x3. Itspopulation was all of the students of Mathematics department of IKIP PGRI Madiun in academicyear 2014/2015. The samples were taken by using the random sampling technique. The data weregathered through test and questionnaire method and its were analyzed by using the unbalanced twowayanalysisofvarianceatthesignificancelevelof5%.The results showed that: (1) the GI and GI-ProblemPosing result in the same good learningachievement; (2) the learning achievement with positive was better than that with neutral andnegative, that with neutral was better than that with negative; (3) in each studentsâ attitudes type,the GI and GI-ProblemPosing result in the same good learning achievement; (4) in general, thelearning achievement with positive was better than neutral and negative, that neutral was betterthan negative. However, if viewed from GI with a positive and neutral have the same achievementand better than negative.Keywords: learning model, GI, Problem Posing, students attitudes towards Mathematics.